Monogenoids (Diplectanidae, Polyonchoinea) from the gills of mojarras (Perciformes, Gerreidae) with the resurrection of Neodiplectanum Mizelle & Blatz, 1941 and the proposal of Darwinoplectanum n. gen. - Domingues, Marcus V.; Diamanka, Arfang; Pariselle, Antoine (Zootaxa, 2011)
Neodiplectanum Mizelle & Blatz, 1941 is resurrected and emended for monogenoids from the gills of gerreid hosts from Western Atlantic: Neodiplectanum wenningeri from Eucinostomus gula (Quoy & Gaimard) [type-host] and Gerres cireneus (Walbaum); N. magnodiscatum (Fuentes Zambrano, 1997) n. comb. (syn. Diplectanum magnodiscatum Fuentes Zambrano, 1997) from Eugerres plumieri (Cuvier); Neodiplectanum gatunense (Mendoza Franco, Roche & Torchin, 2008) n. comb. (syn. D. gatunense Mendoza Franco, Roche & Torchin, 2008) from Eugerres brasilianus (Cuvier); N. mexicanum (Mendoza Franco, Roche & Torchin, 2008) n. comb. (syn. D. mexicanum Mendoza Franco, Roche & Torchin, 2008) from Diapterus rhombeus (Cuvier). Neodiplectanum is characterized for diplectanids with male copulatory organ and accessory piece non-articulated, heavily sclerotised vaginal atrium, ventral anchors with deep root twice as long as superficial root, dorsal anchors with conspicuous superficial and deep roots and squamodiscs with spinelike rodlets in the posterior rows. Darwinoplectanum n. gen. is proposed for species with male copulatory organ articulated to the accessory piece, vaginal opening sinistral, marginal or submarginal; non-sclerotised vagina atrium; and egg ovate with short filament. Here, we described three new species of Darwinoplectanum n. gen. from the gills of gerreid hosts from the Eastern and/or Western Atlantic: Darwinoplectanum figueiredoi n. gen. n. sp. [type species] from Eucinostomus argenteus Baird & Girard; D. amphiatlanticus n. gen. n. sp. from Eucinostomus melanopterus (Bleecker)[Type host] from Africa, and E. argenteus from Brazil; and D. pilittae n. gen. n. sp. from G. cireneus.